Improving the Critical Thinking Skills of Grade III Students through Project-Based Learning in Natural and Social Sciences Subjects at State Elementary School 030/VIII Rimbo Bujang, Tebo - fidiana; Andryadi; Mu’alimin (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research was motivated by the low critical thinking ability of grade III students in Natural and Social Sciences (IPAS) learning at SD Negeri 030/VIII Rimbo Bujang, Tebo, which was shown by the initial completeness of 31.58% or six out of nineteen students. The research aims to describe the application of project-based learning, analyze the improvement of critical thinking skills, and assess the achievement of indicators of action success. The research uses the Kemmis and McTaggart model, Class Action Research, which is carried out in two cycles through the stages of planning, implementation, observation, and reflection. Data were collected through observation of learning implementation, critical thinking ability tests, project assessments, documentation, and field notes; Furthermore, it was analyzed descriptively, quantitatively, and qualitatively. The results showed that the average learning implementation increased from 77.5% in the first cycle in the good category to 92.5% in the second cycle in the very good category. The average score of critical thinking increased from 65.47 to 78.05, while classical completeness increased from 36.84% to 57.89%. Project-based learning increases student participation in observing, discussing, drafting products, presenting findings, and drawing conclusions. It was concluded that project-based learning is effective in improving the quality of the learning process and critical thinking skills, but classical completeness of at least 85% has not been achieved, so a follow-up cycle is needed. The next improvement needs to prioritize individual mentoring, strengthening evidence-based reasons, and formative assessments for students who have not been completed optimally.